The Protection of Zinc against Acute Cadmium Exposure: A Morphological and Molecular Study on a BBB In Vitro Model - Jacopo J. V. Branca; Donatello Carrino; Ferdinando Paternostro; Gabriele Morucci; Claudia Fiorillo; Claudio Nicoletti; Massimo Gulisano; Carla Ghelardini; Lorenzo Di Cesare Mannelli; Matteo Becatti; Alessandra Pacini (Cells, 2022)
Cadmium (Cd) is a well-known occupational and environmental pollutant worldwide, and its toxicity is widely recognised. Cd is reported to increase the permeability of the blood–brain barrier (BBB) and to penetrate and accumulate in the brain. Although many lines of evidence show that Cd toxicity is induced by different mechanisms, one of the best known is the Cd-dependent production of reactive oxygen species (ROS). Zinc is a trace element known as coenzyme and cofactor for many antioxidant proteins, such as metallothioneins and superoxide dismutase enzymes. To date, very little is known about the role of Zn in preventing Cd-induced blood–brain barrier (BBB) alterations. The goal of this study was to test the Zn antioxidant capacity against Cd-dependent alterations in a rat brain endothelial cell line (RBE4), as an in vitro model for BBB. In order to mimic acute Cd poisoning, RBE4 cells were treated with CdCl2 30 µM for 24 h. The protective role of ZnCl2 (50 µM) was revealed by evaluating the cell viability, reactive oxygen species (ROS) quantification, cytochrome C distribution, and the superoxide dismutase (SOD) protein activity. Additionally, the effectiveness of Zn in counteracting the Cd-induced damage was investigated by evaluating the expression levels of proteins already known to be involved in the Cd signalling pathway, such as GRP78 (an endoplasmic reticulum (ER) stress protein), caspase3 pro- and cleaved forms, and BAX. Finally, we evaluated if Zn was able to attenuate the alterations of zonula occludens-1 (ZO-1), one of the tight-junction (TJ) proteins involved in the formation of the BBB. Our data clearly demonstrate that Zn, by protecting from the SOD activity impairment induced by Cd, is able to prevent the triggering of the Cd-dependent signalling pathway that leads to ZO-1 dislocation and downregulation, and BBB damage.